Legal Review of Legality of Amil as Zakat Fitrah Management Outside the Authority of BAZNAS Perspective of Law No. 23 of 2011 Concerning Zakat Management (Case Study of Mosques in Sub-districts) North Binjai ) - Cahyani, Dwi; Iqbal, Muhammad Nur (Journal of Law, Politic and Humanities, 2025)
This study examines the legality of amil zakat as managers of zakat fitrah who do not have authority from BAZNAS based on Law No. 23 of 2011 concerning Zakat Management, which requires that zakat management must be carried out by amil who has written permission from authorized officials such as BAZNAS or the Office of Religious Affairs (KUA). This study aims to determine the process of forming the Amil Zakat Committee at the Istiqomah Mosque, Ar-Rahman Mosque, and Al-Huda Mosque in North Binjai District and a legal review of the legality of the committee. The results of the study indicate that the formation of the committee in the three mosques was carried out through deliberation between mosque administrators, community leaders, and mosque youth, but the committee did not yet have a Decree (SK) from BAZNAS/KUA. The reasons for the delay in registering the SK were due to time constraints and communication difficulties with BAZNAS. Based on Government Regulation No. 14 of 2014 which is the implementation of Law No. 23 of 2011, zakat collectors must obtain written permission from BAZNAS or KUA to obtain legality in managing zakat, so that zakat collector committees that do not fulfill this provision, as happened in the three mosques, cannot be considered valid according to sharia